2012
DOI: 10.1038/ismej.2012.35
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of large-insert, small-insert and pyrosequencing libraries for metagenomic analysis

Abstract: The development of DNA sequencing methods for characterizing microbial communities has evolved rapidly over the past decades. To evaluate more traditional, as well as newer methodologies for DNA library preparation and sequencing, we compared fosmid, short-insert shotgun and 454 pyrosequencing libraries prepared from the same metagenomic DNA samples. GC content was elevated in all fosmid libraries, compared with shotgun and 454 libraries. Taxonomic composition of the different libraries suggested that this was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
19
0
2
Order By: Relevance
“…Replication is fundamental to rigorous experimental design [25], but it is only now becoming financially possible for metagenomic studies [26,27]. Here we examined replicate metagenomes across varied DNA input amounts, library preparation procedures, and sequencing platforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replication is fundamental to rigorous experimental design [25], but it is only now becoming financially possible for metagenomic studies [26,27]. Here we examined replicate metagenomes across varied DNA input amounts, library preparation procedures, and sequencing platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Fosmids had elevated %G + C, which is ascribed to a cloning bias [26]. Among the remaining libraries, we expected a low %G + C shift due to the adaptor-mediated amplification step, commonly attributed to inhibitory effects of high %G + C DNA secondary structures, either during library amplification [30] or downstream emPCR [31].…”
Section: Discussionmentioning
confidence: 99%
“…The functional metagenomic approach presents two different strategies for libraries generation. Primarily, large-insert libraries, constructed in cosmids or fosmids, allow for the stable recovery of large DNA fragments and sequence homology screening purposes [8]. This strategy would also allow the recovery of complete biosynthetic pathways or the functional expression of large multi-enzyme assemblies (as in the case of polyketide synthases or hydrogenases clusters) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, small-insert expression libraries (i.e. lambda phage vectors and plasmids), are constructed for activity screening from single genes or small operons [8]. In this strategy, strong vector expression signals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The general assumption in cloning-based metagenomic approaches is that foreign DNA can be stably maintained in E. coli and that the cloned DNA is a fair representation of the original sample. However, it has been previously observed that fosmid libraries exhibit a GC bias [1, 2]. In general, such cloning biases may affect conclusions derived from analysis of the clone libraries.…”
Section: Introductionmentioning
confidence: 99%